Miss Wondergem's dreadfully dreadful pie - Valerie Sherrard; Wendy J Whittingham (St. John's, N.L. : Tuckamore Books, 2011)
Miss Wondergem's Bakery, coming quite soon! In fact, it will open tomorrow at noon!There's a brand new bakery in town, and no one could be happier about it than Verna, Myrna and Bradley McGrew. As much as they love their mother, the McGrew children dread what comes out of her kitchen and with very good reason. But when the three young McGrews meet the new bakery's owner, they're in for a most unpleasant surprise.